EFFECT OF DEUTERIUM WATER ON BLOOD VALUES AND DIGESTIBILITY OF NUTRIENTS OF RHESUS MACAQUE - Gaponov Nikolay Vasilyevich; Svistunov Sergey Vladimirovich; Bondarenko Nina Nikolaevna; Romanenko Irina Aleksandrovna (Scientific Journal of Pedagogy and Economics, 2020)
The use of water with a modified isotopic composition in the diet of humans and animals, for example, with a reduced deuterium content, affects the rate of biological processes. In this regard, the targeted formation of the isotopic D / H gradient in the body can be used to increase its adaptive properties to external influences. Primates have a high anatomical and physiological similarity with humans, therefore, are an indispensable model for reproducing various pathological and toxic conditions in humans. The aim of the study was to study the effect of water with a low deuterium content on the hematological and biochemical blood parameters of rhesus monkeys and on the digestibility of nutrients of the diet. In the control group, primates consumed water with a natural regional content of deuterium equal to 150 mg / l, and in the experimental group - with reduced to 50 mg/l. The duration of the experiment was 35 days. The material for the study was venous blood, serum and feces of primates. Blood was drawn from monkeys before the use of deuterium depleted water and after the completion of the experiment. All blood samples (2.5-3.0 ml) were taken from the cubital or femoral veins of animals on an empty stomach and stabilized with a heparin solution. Laboratory studies of animal blood were performed on an automatic hematological analyzer (Beckman Coulter, USA) of the CoulterAcT 5diffCP brand. In order to study the effect of water with a reduced deuterium content on hematological parameters, we determined the number of red blood cells, white blood cells, platelets, hemoglobin concentration, hematocrit, the average volume of red blood cells, red blood cell anisocytosis, and erythrocyte sedimentation rate (ESR). The metabolism trial was divided into two periods. Preliminary - to exclude the influence of previous feeding and accustoming primates to cage conditions of keeping. Experimental - conducting a thorough accounting of consumed feed, excreted excrement. Feces were collected daily at the same time (morning and evening), weighed and ground in a mortar. At each collection, 50% of the homogenized mass was taken for analysis. The collected portions were stored in the refrigerator. After the end of the experimental (accounting) period in the collected feces, the initial moisture was determined by drying at 60-70 ℃ to constant weight. The resulting air-dry mass was thoroughly ground and analyzed. It has been found that the introduction of water with a reduced deuterium content into the diet of primates has a positive effect on feed conversion rate and blood biochemical parameters.